Radon Concentration in Biological Samples of Smokers and Non-smokers Using Lexan Detector - Alkufi, A. A.; Abojassim, A. A.; Oleiwi, M. H. (Atom Indonesia, 2024)
This study was conducted in the Najaf Governorate, Iraq, to analyze radon concentration in biological samples from smokers and non-smokers. The samples, including blood serum, urine, hair, and nails, were used as biomarkers to determine the presence or absence of radon (222Rn). Using a natural exposure method, the nuclear track detector (Lexan, Belgium) was utilized to measure these radon concentrations in the samples. Seventy-five samples of blood serum, urine, hair, and nails were collected for smokers of healthy people and fifty samples for non-smokers of healthy people in five age groups. This study was based on age and smoking to compare the results and determine their effects on radon concentrations. The results show that the average values of radon concentrations (in Bq/m3) in blood serum, urine, hair, and nails for smokers were 54.7 ± 22.1, 62.9 ± 23.1, 34.7 ± 11.2, and 41.7 ± 15.2, respectively. Meanwhile, the average values of radon concentrations (in Bq/m3) in blood serum, urine, hair, and nails for non-smokers were 24.2 ± 6.0, 30.0 ± 6.3, 18.7 ± 5.2, and 21.6 ± 6.9 respectively. The results and comparisons indicate that radon concentrations depend on the variables on which this study was based (age and smoking). Smokers and non-smokers had different levels of radon in all biological samples. The P-value was